Projeto Semear: um espaço para o Serviço de Convivência e Fortalecimento de Vínculos de crianças e adolescentes - Oliveira, Júlio Rodrigues de [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
O seguinte trabalho consiste no anteprojeto arquitetônico de um Núcleo para a realização do Serviço de Convivência e Fortalecimento de Vínculos direcionado à crianças e adolescentes de 6 a 15 anos em situação de vulnerabilidade social, localizado no Conjunto Habitacional Isaura Pitta Garms, na cidade de Bauru (SP). O objetivo é promover um espaço adequado para a realização das atividades que compõem este serviço socioassistencial, através da promoção de acessibilidade, estratégias para conforto ambiental e ludicidade nos espaços. O projeto busca fornecer protagonismo ao espaço livre da edificação, entendendo o seu potencial para as dinâmicas de convivência entre os usuários do espaço, além da conexão com o entorno e comunidade local.

The following work consists of the preliminary architectural design for a Center aimed at providing the Service for Socialization and Strengthening of Bonds (SCFV), directed towards children and adolescents aged 6 to 15 in situations of social vulnerability. The project is located in the Isaura Pitta Garms Housing Complex, in the city of Bauru, São Paulo, Brazil. Its objective is to create an adequate space for the activities encompassed by this social assistance service, emphasizing accessibility, environmental comfort strategies, and playfulness in the design of the spaces. The project seeks to prioritize the open spaces of the building, recognizing their potential to foster social interactions among users, as well as their connection to the surroundings and the local community.
Sowing Project: a Space for the Service of Coexistence and Strengthening of Bonds for Children and Adolescents
Proyecto Semear: Un espacio para el Servicio de Convivencia y Fortalecimiento de Vínculos para niños y adolescentes
Keywords: Arquitetura social; Serviço de Convivência e Fortalecimento de Vínculos; Crianças e adolescentes; Vulnerabilidade social; Social architecture; Service for socialization and strengthening of bond; Children and adolescents; Social vulnerability